O Programa Institucional de Bolsa de Iniciação à Docência e a formação do pedagogo: limites e potencialidades - Silva, Maria de Lourdes de Almeida (2015)
This research aims to investigate the limits and potential of the Institutional Scholarship Program for Teaching Initiation (Pibid) in the formation of the pedagogue. It is a qualitative case study in a Higher Education Institution (IES) of the Federal District and in a first-year public elementary school. Both entities have in common the development of partnership activities with Pibid. The IES was chosen because it had the highest number of Program participants receiving scholarships in the Federal District in the year 2014. Semi-structured interviews, focus groups, and questionnaires were used as research techniques. The data was interpreted in light of the content analysis approach, based on Bardin (2010), Moraes (1999), and Franco (2008). The research subjects includes students, IES administrators, and school principal and supervising teachers from the public school. Students who were not on scholarships were also interviewed. The study showed that the participation of students in Pibid promotes the dynamism of activities in the classroom, beyond contributing to a pedagogical construction more focused on group actions and discussions on the pedagogical processes. The study reveals the potential of Pibid as teacher training policy which promotes awareness to school reality and is presented as an important facilitator between theory and practice in initial training of teachers who receive scholarship aid. However, the Pibid selection criteria limits the opportunity to only a few students and highlights the fragility of the supervised training part of the course, which presents large gaps as a curricular component responsible for linking theory, research, practice, and reflection. The development of Pibid has promoted the debate on the role of IES and public schools in the initial training of basic education teachers in Brazil. The study points to the need for greater investment and attention to the initial training processes offered to the future teacher, responsible for early childhood education and the early years of basic education. The improvement of teacher education demands the commitment of all stakeholders involved in this process.